Use of Gypsum as a Good Stationary Phase in Thin Layer Chromatography and Relation between Rfs and Dipole Moments of Some Organic Compounds - Amoozadeh, A.; Zavvar Mousavi, H. (Asian Journal of Chemistry, 2010)
In this paper, the preparation of gypsum TLCs and its utility for a variety of organic compounds have been reported. In addition, dipole moments of some organic compounds have been calculated by AM1 semi-empirical method and drew the Rfs of these compounds in gypsum TLCs versus their dipole moments. The results showed that a linear correlation exist between Rfs and dipole moments. Finally, by theoretical calculations in AM1 method, the dipole moments of some other organic compounds are obtained and their Rfs on gypsum TLCs are predicted. The experimental results on gypsum TLCs show good agreements with the theoretical results.